Adel Selim (1926 - 1978), His Life and Political Role - Othman , Burhan Hatam (Zanco Journal of Human Sciences, 2021)
Adel Salim, who was one of the well-known Erbil figures, had a prominent and significant political role in the rank of the Iraqi Communist Party. In the forties and fifties of the last century, he was in charge of part of the Baghdad underground organizations, and in the sixties and seventies he worked as a professional party cadre in Irbil, Sulaymaniyah, Kirkuk, Mosul and the Kurdistan branch of the Iraqi Communist Party. In addition to his role and positions before, during and after the National Front between the Communist Party and the ruling Baath Party in 1973. During the years of his political struggle, Adel Saleem was subjected to persecution, detention and torture, and he spent 12 years completely in Iraqi prisons and exiles, specifically during the monarchy and the first republican era. This research deals with aspects of Adel Selim's life and political struggle between the years (1926-1978), and it consists of four main axes: The first axis: A brief overview of the history of his family, the beginning of his life and the stages of his studies. The second axis: Adel Salim's political struggle between the years (1941-1956), highlighting his struggle within the ranks of the Iraqi Communist Party, and his persecution, arrest and torture by the Iraqi security services. The third axis: Adel Salim's political stances and struggle between the years (1965-1970), where Adel Saleem worked during this period in many regions of Kurdistan, specifically in Erbil, Kirkuk and Sulaymaniyah. He was an effective member of the Kurdistan Regional Office of the Iraqi Communist, and he played a prominent role in his party's various activities. As for the fourth and last axis, it is devoted to the role and struggle of Adel Selim both politically and administratively which was between the years (1970-1978). As they touched on the political role of Adel Saleem, his opposing stances towards the National Front and the Baath Party, and his continuous criticisms at the Front's meetings in the presence of senior Baath Party officials. In addition to his tenure in the position of Secretary-General of Transport and Communications and his work in the Executive Council of the Kurdistan Region, then he was dismissed by a decision of the President of the Republic Ahmed Hassan Al-Bakr, and then he was poisoned and eliminated by the Ba'athist regime on 9/12/1978.